Análise in vitro do efeito do ácido hialurônico nos mecanismos parácrinos das células estromais mesenquimais adipo-derivadas para regeneração óssea - Cabreira, Carina Lantmann (2019)
Tissue engineering is a growing field for the regeneration of bone defects, with potential to overcome the limitations of bone grafting techniques currently available. Mesenchymal stromal cells have demonstrated great potential for use in this field because of their multipotency, these cells secrete a range of cytokines and growth factors stimulating neighboring cells in tissue growth and repair. Several types of matrices for the support of the mesenchymal stromal cells have been developed, and the use of hyaluronic acid presented promising results. The present research aimed to evaluate in vitro the influence of the matrix of low molecular weight hyaluronic acid (AH-BP) and high and low molecular weight (AH-ABP) combined in the paracrine mechanism of the mesenchymal stromal cells derived from adipose tissue, differentiated or not in osteoblasts. Stromal cells were isolated from the adipose tissue of Lewis rats, expanded and characterized. The cytotoxicity assay was performed through the MTT test to evaluate cell viability in the presence of hyaluronic acids. For the evaluation of the dosage of growth factors, an ELISA assay was performed. The cells in the 4th passage were seeded in 6-well plates, in triplicate, grown for 30 days in a humidified oven at 37 ° C and 5% CO2 in the atmosphere, and divided into 6 groups: (G1) ASC; (G2) ASC + AH-ABP; (G3) ASC + AHBP; (G4) OSTEO; (G5) OSTEO + AH-ABP; (G6) OSTEO + AH-BP. The ASCs were cultured in complete medium for 27 days, in groups 2 and 3 the respective AH was added end maintained for a further 3 days. OSTEO cells were cultured in osteogenic differentiation medium for 27 days, in groups 5 and 6 the HA was added and maintained for a further 3 days. The results showed that the highest values of growth factor secretion occurred in the group of ASCs in complete medium and of these, when AH-ABP was added. After 27 days in osteogenic medium, the cells differentiated into osteoblasts had low levels of secretion of growth factors. The use of AH-BP had low expression in relation to osteoinduction of the factors, when compared with the use of AH-ABP. According to the results, the differentiated cells secreted fewer factors than the ASCs, with significant statistical difference. Expression of VEGF, FGF and BMP-2 was significantly higher in ASCs and ASCs + AH-ABP. The IGF-1 growth factor presented the highest expression in the ASC + AH-BP group, with a significant difference in the other groups. It was found that the use of undifferentiated cells in a future cell compound appeared to be more favorable than the use of these already differentiated cells in osteoblasts. Advanced periods of differentiation seemed to lead to reduced osteoinduction. From this study we observed that the AH-ABP matrix together with ASCs has the potential to positively influence bone tissue repair through increased secretion of osteogenic growth factors, compared to the use of the other AH-BP matrix.